Estimated burden of serious fungal infections in Togo. Issue 12 (13th October 2021) - Dorkenoo, Ameyo M.; Adjetey‐Toglozombio, Akovi K.; Ocansey, Bright K.; Sossou, Efoe; Lack, Fiali; Denning, David W.
Abstract: Background: Over the years, the focus of infectious diseases in many African countries has been mainly on viral, bacterial and parasitic infections. Serious fungal infections (SFIs) with comparable morbidity rate in these countries remain neglected. Objectives: To estimate the burden of SFI in Togo and to stimulate efforts for improved attention. Methods: Literature was thoroughly searched for epidemiological data on SFI in Togo. Incidence and/or prevalence of SFI was estimated using socio‐demographics, health system's information, risk‐groups data and SFI rates obtained from national and international studies. Results: About 5.29% of the 7, 265, 286 Togolese population is estimated to suffer from SFI annually. Among HIV patients, 1, 342, 1, 650 and 330 may develop cryptococcal meningitis, Pneumocystis pneumonia and disseminated histoplasmosis respectively per year. Oral and oesophageal candidiasis may annually affect 19, 800 and 7, 535 persons, respectively, living with HIV. Estimated incidence of invasive aspergillosis (IA) was 283 cases. Prevalence of chronic pulmonary aspergillosis (CPA) was estimated at 191 cases. The annual incidence of allergic bronchopulmonary aspergillosis (ABPA) and severe asthma with fungal sensitization (SAFS) was 4, 577 and 6, 042 cases, respectively. Tinea capitis and recurrent Candida vaginitis presumably affect 232, 271 children and 108, 979 women respectively. Candidaemia incidence is estimated at 5 cases per 100, 000 inhabitants and fungal keratitis may affect 981 persons annually. Conclusions: SFIs in Togo are probably more significant than expected. These findings underscore the need to increase awareness among healthcare professionals, enhance diagnostic and therapeutic capacities and intensify epidemiological studies for effective management of fungal infections in Togo.